Does cholecystectomy affect the sphincter of oddi and the ampulla of vater? - Skalicky, Marjan (Acta Medico-Biotechnica, 2021)
Purpose: About 20-50% of cholecystectomized patients complain of dyspeptic problems after gallstone surgery. I hypothesized that some of these problems do not arise from primary gallbladder disease, but are due to problems of duodenal origin. Methods: I examined 80 patients using endoscopic ultrasound (EUS) before gallstone surgery (AOP). I repeated the examination 3 months (POP3) and 6 months (POP6) after the surgery. Fifty patients who underwent surgery were symptomatic; 30 were asymptomatic. In all patients, an analysis of the papilla of Vater (PV) was carried out with a special focus on the visibility of the sphincter of Oddi complex (SOC) and the ampulla of papilla (AP). Results: The visibility of the SOC was significant in the measurements AOP/POP3 (p<0.05). The comparison POP3/POP6 (p<0.001) was also significant. The behavior pattern of the AP (AOP/POP3, POP3/POP6, AOP/POP6) in various measurements was not significant (p>0.05). The linear percentage increase of non-visible AP (76%, 78%, and 80%) indicated different changes in the mechanism with respect to visibility of the SOC; 52% (AOP), 72% (POP3) and 50% (POP6). Conclusions: These data showed that cholecystectomy affected the visibility of the SOC. The AP, with its embryological and histological disposition based on a duodenal pattern (SOC is based on a biliary pattern), showed non-significant linear trends of increased non-visibility.